Getting Up Close and Personal With Climate Scientists in Thin Ice. Issue 5 (4th February 2014) - Weiss, Peter
<x xml:space="preserve">Abstract</x> In a new documentary screened at the 2013 Fall Meeting, viewers follow the wanderings of Simon Lamb, a New Zealand geologist on a mission. Lamb is out to explore firsthand the research that climate scientists do and to gauge whether their claims that human‐made emissions are changing Earth's climate are correct.